2024
DOI: 10.1161/strokeaha.123.046122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermittent Oro-Esophageal Tube Feeding in Bulbar Palsy After Ischemic Stroke: A Randomized Controlled Study

Hongji Zeng,
Weijia Zhao,
Junfa Wu
et al.

Abstract: BACKGROUND: Nasogastric tube feeding (NG) has been widely used in patients with bulbar palsy after ischemic stroke but is associated with a significant risk of complications including malnutrition and pneumonia. Intermittent oro-esophageal tube feeding (IOE) can help alleviate these concerns. This study explored the clinical effect of IOE versus NG on nutritional status, swallowing function, stroke-associated pneumonia, and depression in patients with bulbar palsy after ischemic stroke. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Therefore, this study investigated the risk factors for malnutrition in SPBP to help identify high-risk patients at an early stage. This study demonstrated a pneumonia prevalence of 60% in SPBP, consistent with a clinical study conducted in China ( 27 ). Logistic regression analysis revealed that pulmonary infection is an independent risk factor.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, this study investigated the risk factors for malnutrition in SPBP to help identify high-risk patients at an early stage. This study demonstrated a pneumonia prevalence of 60% in SPBP, consistent with a clinical study conducted in China ( 27 ). Logistic regression analysis revealed that pulmonary infection is an independent risk factor.…”
Section: Discussionsupporting
confidence: 91%
“…The current study showed that the prevalence of malnutrition in SPBP was 60.59%, significantly higher than the overall prevalence of malnutrition in the stroke survivors enrolled (51.01%, p < 0.05). Possible reasons for this include the fact that the lesions in patients with true bulbar palsy are located in the medulla oblongata, which is the most basic center for regulating swallowing function ( 27 ). Therefore, SPBP typically experience severe dysphagia, manifested as difficulty in eating, inability to swallow food after chewing, choking on liquids, and in severe cases, inability to conduct oral intake, which can potentially lead to malnutrition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations